Gas‐Separation Membranes Loaded with Porous Aromatic Frameworks that Improve with Age1. (13th January 2015) - Lau, Cher Hon; Konstas, Kristina; Thornton, Aaron W.; Liu, Amelia C. Y.; Mudie, Stephen; Kennedy, Danielle F.; Howard, Shaun C.; Hill, Anita J.; Hill, Matthew R.
Abstract Porosity loss, also known as physical aging, in glassy polymers hampers their long term use in gas separations. Unprecedented interactions of porous aromatic frameworks (PAFs) with these polymers offer the potential to control and exploit physical aging for drastically enhanced separation efficiency. PAF‐1 is used in the archetypal polymer of intrinsic microporosity (PIM), PIM‐1, to achieve three significant outcomes. 1) hydrogen permeability is drastically enhanced by 375 % to 5500 Barrer. 2) Physical aging is controlled causing the selectivity for H2 over N2 to increase from 4.5 to 13 over 400 days of aging. 3) The improvement with age of the membrane is exploited to recover up to 98 % of H2 from gas mixtures with N2. This process is critical for the use of ammonia as a H2 storage medium. The tethering of polymer side chains within PAF‐1 pores is responsible for maintaining H2 transport pathways, whilst the larger N2 pathways gradually collapse.